2015
DOI: 10.1080/1550428x.2015.1011818
|View full text |Cite
|
Sign up to set email alerts
|

How Law Shapes Experiences of Parenthood for Same-Sex Couples

Abstract: The authors wish to thank Kimberly Tyler, Julia McQuillan, and Helen Moore for their helpful comments and suggestions. We also thank the families who generously shared their stories. Abstract Gay, lesbian, and bisexual (GLB) parents are increasingly common and visible, but they face a number of social and legal barriers in the United States. Using legal consciousness as a theoretical framework, we draw on data from 51 interviews with GLB parents in California and Nebraska to explore how laws impact experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 58 publications
1
49
0
Order By: Relevance
“…All had used an unknown donor "in order to avoid any threats to their custody rights by a donor" (p. 758). Park et al (2015) corroborate this finding, showing that some respondents chose to use an unknown donor through a sperm bank to eliminate the possibility that someone else could make a legal claim to the child. Those who use known donors often work with a lawyer to execute a donor agreement that stipulates the intended arrangement (Chabot and Ames 2004).…”
Section: Becoming a Parentmentioning
confidence: 55%
See 3 more Smart Citations
“…All had used an unknown donor "in order to avoid any threats to their custody rights by a donor" (p. 758). Park et al (2015) corroborate this finding, showing that some respondents chose to use an unknown donor through a sperm bank to eliminate the possibility that someone else could make a legal claim to the child. Those who use known donors often work with a lawyer to execute a donor agreement that stipulates the intended arrangement (Chabot and Ames 2004).…”
Section: Becoming a Parentmentioning
confidence: 55%
“…In contrast, they thought that surrogacy was the most legally secure route to parenthood to pursue. These findings were corroborated by Park et al (2015). They analyzed data from 51 gay and lesbian parents in California and Nebraska.…”
Section: Becoming a Parentmentioning
confidence: 71%
See 2 more Smart Citations
“…Previous scholarly work has demonstrated that intentions of fertility and aspirations of parenthood are likely different for LGBs than for heterosexuals, 31,32 potentially influenced by legal regulations (e.g., prohibitions surrounding same-sex marriage, adoption, or surrogacy), 33 as well as negative social attitudes and discriminatory practices that have created obstacles to parenthood, 34 and have impeded access to fertility services for LGB individuals and same-sex couples. The implicit and explicit messages of heterosexual bias are grounded in stigmatizing narratives that perpetuate the belief that LGB individuals are morally unfit to parent, and claim that children who have LGB parents will experience emotional and psychological harm.…”
Section: Fp For Lgb Ayas With Cancermentioning
confidence: 99%